Pani - Sami, Mustafa (book group Karachi, 2010)
The word "Pani" in Urdu simply means "Water." It's a fundamental substance essential for life. Water is used for various purposes, including drinking, cooking, cleaning, and agriculture. It's also crucial for the survival of plants and animals.